Smart biogas: An independent energy system based on organic waste integrated with IoT - Asminar; Abdul Djohar; Syahran Rifaldi; Rifki; Muhammad Adam Raswadi; Arya Sadewa (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Indonesia faces substantial challenges in waste management, as most organic waste remains untreated. A similar situation occurs in Kendari City, which generates approximately 253 tons of waste per day, the majority of which consists of organic materials. This condition reflects the untapped potential of renewable energy derived from organic waste, thereby necessitating the development of an effective system to address these issues comprehensively. Methods: This study employed a descriptive research method with a case study approach. The data analyzed encompassed the volume and composition of organic waste in Kendari City. The findings served as the foundation for designing a Smart Biogas system integrated with the Internet of Things (IoT). The system incorporates sensors to monitor temperature, pressure, and methane concentration in real time and is connected to an application that enables remote monitoring and control. Findings: The study revealed that the potential biogas production from organic waste in Kendari City could reach approximately 5,650 m³ per day. This volume demonstrates significant potential to meet a portion of the local energy demand. By adopting a communal-based system design, the utilization of biogas can be optimized, particularly to support energy needs at the sub-district level. Conclusion: The results indicate that the implementation of the Smart Biogas system can not only reduce the volume of organic waste but also provide a sustainable energy independence solution. Novelty/Originality of this article: The novelty of this research lies in the development of a Smart Biogas system integrated with IoT technology, specifically designed for communal-scale applications. The system enables real-time monitoring of the fermentation process through temperature, pressure, and methane sensors, with remote access facilitated by an integrated application. This approach ensures that organic waste is not only effectively managed but also converted into renewable energy, thereby supporting local energy independence.